Association between marital status and cognitive function in Japan: results from the Toyama Dementia Survey. Issue 4 (25th May 2021) - Nakahori, Nobue; Sekine, Michikazu; Yamada, Masaaki; Tatsuse, Takashi; Kido, Hideki; Suzuki, Michio
Abstract : Background: This study aims to clarify the association between marital status and dementia in Japan, adjusting for socioeconomic, lifestyle, and lifestyle‐related disease factors. Methods: Data from the Japanese Toyama Dementia Survey were used. Individuals aged ≥65 years living in Toyama Prefecture were randomly selected, and 1171 participants were analysed, with a sampling rate of 0.5%. The participants' marital status, socioeconomic status, lifestyle factors, and lifestyle‐related diseases were assessed. The odds ratio (OR) of marital status for each lifestyle factor and medical histories were calculated by logistic regression analysis. The OR of marital status for dementia was also calculated by logistic regression analysis. Results: The prevalence of dementia was 7.4% for married, and 20.6% for non‐married participants. Non‐married participants showed a higher prevalence of a history of stroke than married participants. The age‐ and sex‐adjusted OR of marital status for dementia was 1.99 (95% confidence interval (CI) 1.24–3.18) for non‐married compared with married participants. Following variable adjustments, the OR for dementia was higher for non‐married participants (adjusted OR 1.71; 95% CI 1.03–2.85). Conclusions: Non‐marital status was an independent risk factor for dementia in Japan even after adjusting for socioeconomic, lifestyle, and lifestyle‐related disease factors. Non‐married people were more likely to have dementia because of their history of stroke.